Cluster Candidates with Massive Quiescent Galaxies at z ∼ 2 - Tomokazu Kiyota; Makoto Ando; Masayuki Tanaka; Alexis Finoguenov; Sadman Shariar Ali; Jean Coupon; Guillaume Desprez; Stephen Gwyn; Marcin Sawicki; Rhythm Shimakawa (The Astrophysical Journal, 2025)
Galaxy clusters are crucial to understanding the role of the environment in galaxy evolution. However, due to their rarity, only a limited number of clusters have been identified at z  ≳ 2. In this paper, we report a discovery of seven cluster candidates with massive quiescent galaxies at z  ∼ 2 in the 3.5 deg ^2 area of the XMM Large Scale Structure field, roughly doubling the known cluster sample at this frontier redshift if confirmed. We construct a photometric redshift catalog based on deep ( i  ∼ 26, K _s  ∼ 24) multiwavelength photometry from the u * band to the K band gathered from the Hyper Suprime-Cam Subaru Strategic Program and other collaborative/public surveys. We adopt a Gaussian kernel density estimate with two different spatial scales (10″ and 60″) to draw a density map of massive ( $\mathrm{log}({M}_{* }/{M}_{\odot })\gt 10.5$ ) and quiescent ( $\mathrm{log}(\mathrm{sSFR}\,[{\mathrm{yr}}^{-1}])\lt -10$ ) galaxies at z  ∼ 2. Then, we identify seven prominent overdensities. These candidates show clear red sequences in color–magnitude diagrams ( z  −  H versus H ). Moreover, one of them shows an extended X-ray emission with L _X  = (1.46 ± 0.35) × 10 ^44 erg s ^−1 , suggesting its virialized nature. There is no clear evidence of enhancement nor suppression of the star formation rate of the main-sequence galaxies in the clusters. We find that cluster galaxies have a higher fraction of transition population with $-10.5\lt \mathrm{log}(\mathrm{sSFR}\,[{\mathrm{yr}}^{-1}])\lt -10$ (12%) than the field (2%), which implies the ongoing star formation quenching. The quiescent fraction in the cluster candidates also exceeds that in the field. We confirm that the excess of a quiescent fraction is larger for higher-mass galaxies. This is the first statistical evidence for the mass-dependent environmental quenching at work in clusters even at z  ∼ 2.